Public-private partnership role in development of innovative system of the Republic of Kazakhstan. (Journal of Economic Research & Business Administration, 2016)
Innovations play strategically important role in the long-term economic growth of Kazakhstan. Commercialization of researches results and developments through establishment of the steady relations between science and the market and activization of a transfer of technologies, is a key task for Kazakhstan. Recently in economic researches the considerable attention is given to problems of innovations and businesses that is caused by increasing of a role of technological development as a factor of competitiveness of firm and the countries. Practically at all enterprises increase of competitiveness by improve of quality of production, decrease in its prime cost, extension of the nomenclature and the range of the let-out products was the purpose of technological innovations. In the world there are some models of influence of interaction of science and the industry of public sector, and respectively there are various ways of introduction of an innovation, one of them public-private partnership.